Stabilization of Teeth After Exposure to High Temperature Conditions for Forensic Identification: A Scoping Review - Siti Salsabila Kirana; Gusaimas M. H. H. Akbar (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Teeth are used as a primary method of forensic identification due to their robust nature. Although resistant to various environmental destruction, prolonged exposure to extreme temperatures may alter the tissue, rendering it fragile and prone to fragmentation. This poses a challenge for forensic odontologists in postmortem identification, as postmortem dental analysis often requires teeth to be intact for further investigation beyond the crime scene. This article aims to examine and discuss methods of teeth stabilization following exposure to high temperatures, focusing on materials selection and key properties for selecting the optimum stabilizing agents to preserve/reinforce the heat-affected teeth. Review: The literature review was performed using PubMed and ScienceDirect in accordance with the PRISMA workflow, including only full papers and original research and/or case reports. Various natural and synthetic solutions were effective for teeth stabilization, with spraying as the most effective method for maximum surface coverage. Aside from ease of use, material availability, rapid curing time, and non-volatility, the long-term durability and chemical stability are crucial factors in selecting the appropriate stabilizing agent to store heat-affected teeth for archiving. Conclusion: In conjunction with proper teeth stabilization methods, forensic odontologists must also consider proper storage of evidence, planning a safe route from the crime scene to the mortuary, and evidence storage time for possible future analysis to ensure the best evidence preservation.